(untitled) (World Bulletin of Public Health, 2025)
The consequences of a stroke directly or indirectly affect various organs and systems, including the oral cavity. The most common direct consequence is sialorrhea and pain syndrome, and due to motor disorders, patients have significant difficulties in maintaining oral hygiene, which in turn leads to various dental problems. In this study, an analysis of the state of the oral cavity in stroke patients was carried out, considering the type of acute cerebrovascular accident, post-stroke complications and risk factors. Most patients were found to have an unsatisfactory state of oral hygiene, signs of gingivitis and periodontitis, which indicates the need to develop protocols for the prevention, treatment and prosthetics of stroke patients.